Ion Injection Triggered EMICWaves in the Earth’s Magnetosphere - Remya, B.; Sibeck, D.G.; Halford, A.J.; Murphy, K.R.; Reeves, G.D.; Singer, H.J.; Wygant8, J.R.; Perez, G. Farinas; Thaller, S.A. (My University, 2018)
We present Van Allen Probe observations of electromagnetic ion cyclotron (EMIC) waves triggered solely due to individual substorm-injected ions in the absence of storms or compressions of the magnetosphere during 9 August 2015. The time at which the injected ions are observed directly corresponds to the onset of EMIC waves at the location of Van Allen Probe A (L = 5.5 and 18:06 magnetic local time). The injection was also seen at geosynchronous orbit by the Geostationary Operational Environmental Satellite and Los Alamos National Laboratory spacecraft, and the westward(eastward) drift of ions(electrons) was monitored by Los Alamos National Laboratory spacecraft at different local times. The azimuthal location of the injection was determined by tracing the injection signatures backward in time to their origin assuming a dipolar magnetic field of Earth. The center of this injection location was determined to be close to ∼20:00 magnetic local time. Geostationary Operational Environmental Satellite and ground magnetometer responses confirm substorm onset at approximately the same local time. The observed EMIC wave onsets at Van Allen Probe were also associated with a magnetic field decrease. The arrival of anisotropic ions along with the decrease in the magnetic field favors the growth of the EMIC wave instability based on linear theory analysis.
Keywords: Magnetosphere; Electromagnetic ion cyclotron; EMIC waves; Van Allen Probe